Impact of mhealth messages and environmental cues on hand hygiene practice among healthcare workers in the greater Kampala metropolitan area, Uganda: study protocol for a cluster randomized trial - Richard K. Mugambe; Jane Sembuche Mselle; Tonny Ssekamatte; Moses Ntanda; John Bosco Isunju; Solomon T. Wafula; Winnifred K. Kansiime; Prossy Isubikalu; David Ssemwanga; Habib Yakubu; Christine L. Moe (BMC, 2021)
Abstract Background Hand hygiene (HH) among healthcare workers (HCWs) is critical for infection prevention and control (IPC) in healthcare facilities (HCFs). Nonetheless, it remains a challenge in HCFs, largely due to lack of high-impact and efficacious interventions. Environmental cues and mobile phone health messaging (mhealth) have the potential to improve HH compliance among HCWs, however, these remain under-studied. Our study will determine the impact of mhealth hygiene messages and environmental cues on HH practice among HCWs in the Greater Kampala Metropolitan Area (GKMA). Methods The study is a cluster-randomized trial, which will be guided by the behaviour centred design model and theory for behaviour change. During the formative phase, we shall conduct 30 key informants' interviews and 30 semi-structured interviews to explore the barriers and facilitators to HCWs' HH practice. Besides, observations of HH facilities in 100 HCFs will be conducted. Findings from the formative phase will guide the intervention design during a stakeholders' insight workshop. The intervention will be implemented for a period of 4 months in 30 HCFs, with a sample of 450 HCWs who work in maternity and children's wards. HCFs in the control arm will receive innovatively designed HH facilities and supplies. HCWs in the intervention arm, in addition to the HH facilities and supplies, will receive environmental cues and mhealth messages. The main outcome will be the proportion of utilized HH opportunities out of the 9000 HH opportunities to be observed. The secondary outcome will be E. coli concentration levels in 100mls of hand rinsates from HCWs, an indicator of recent fecal contamination and HH failure. We shall run multivariable logistic regression under the generalized estimating equations (GEE) framework to account for the dependence of HH on the intervention. Discussion The study will provide critical findings on barriers and facilitators to HH practice among HCWs, and the impact of environmental cues and mhealth messages on HCWs' HH practice. Trial registration ISRCTN Registry with number ISRCTN98148144 . The trial was registered on 23/11/2020.